PENGEMBANGAN MEDIA VIDEO ANIMASI PENCEGAHAN BULLYING UNTUK MENUMBUHKAN SIKAP EMPATI PADA ANAK USIA DINI - Nisa, Aliyatun; Reza, Muhammad; Rakhmawati, Nur Ika Sari; Fitri, Ruqoyyah (Universitas Muhammadiyah Ponorogo, 2025)
Bullying problems, especially in early childhood, still often occur and can hurt children's social-emotional development. Bullying prevention efforts need to be carried out early on, one of which is fostering empathy in children. Animated video media is considered an interesting and effective media for fostering empathy in early childhood. This study was conducted to develop animated video media for bullying prevention to foster empathy in early childhood. The research method used is research and development (RD) with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The media was validated by material and media experts, producing analysis scores of 90% and 92.8%. The results of the study showed that the Wilcoxon test that had been carried out, namely the Test Statistics Wilcoxon Test. Asymp. Sig. (2-tailed) showed a value of 0.001 so that p 0.05 or 0.001 0.05, because the results of the significance were less than 0.05, Ho was rejected and Ha was accepted. This shows that there is an average difference between the pretest and posttest results, which experienced an increase in score. So, the conclusion of this study, namely the development of integrated bullying prevention animation video media, is that it is feasible and effective to be used to foster empathy in early childhood.